1999
DOI: 10.1139/z99-141
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nest-site vegetation and predator community on the success of artificial songbird nests

Abstract: Vegetation characteristics are commonly invoked to explain differential nesting success, but few studies have identified how habitat attributes may be associated with specific predator groups responsible for nest losses. We measured vegetation characteristics at artificial songbird nests deployed on and above the ground in mixedwood forest in west-central Alberta, to discriminate characteristics of successful nests from those of nests destroyed by mice and voles, squirrels, and birds. Successful nests, and tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…We provide experimental evidence that the predatory behavior of fish crows in an aviary was principally influenced by the visibility of artificial nests. Our results are consistent with opportunistic observations and inferences derived from field studies, which suggest that visibility is a frequent correlate of nest discovery by corvids in communities where they are known to be active nest predators (Harriman and Berger 1986, Sugden and Beyersbergen 1986, 1987, Yahner and Cypher 1987, Major 1990, Rangen et al 1999). For example, Sugden and Beyersbergen (1987) demonstrated that American crows Corvus brachyrhynchos were less likely to prey on concealed (<20% visible) simulated duck nests than more visible nests, and that nest survival increased with cover height and density.…”
Section: Discussionsupporting
confidence: 91%
“…We provide experimental evidence that the predatory behavior of fish crows in an aviary was principally influenced by the visibility of artificial nests. Our results are consistent with opportunistic observations and inferences derived from field studies, which suggest that visibility is a frequent correlate of nest discovery by corvids in communities where they are known to be active nest predators (Harriman and Berger 1986, Sugden and Beyersbergen 1986, 1987, Yahner and Cypher 1987, Major 1990, Rangen et al 1999). For example, Sugden and Beyersbergen (1987) demonstrated that American crows Corvus brachyrhynchos were less likely to prey on concealed (<20% visible) simulated duck nests than more visible nests, and that nest survival increased with cover height and density.…”
Section: Discussionsupporting
confidence: 91%
“…Lyrebird nests are highly vulnerable to native predatory birds (Lill ; Dalziell & Welbergen ) and, by selecting sites with greater vegetative concealment, reproductive output should be greater (Møller ; Rangen et al . ; Colombelli‐Négrel & Kleindorfer ). The concealment hypothesis is supported by a strong positive influence of structural complexity of understorey vegetation (high strata) on nest site location in the local‐scale model.…”
Section: Discussionmentioning
confidence: 99%
“…This may occur when predators use non‐visual stimuli for nest detection (e.g. Rangen et al . 1999 obs) and/or because a trade‐off exists between nest crypsis and the ability of parents at the nest to detect predators and thus take mitigating action (Gotmark et al .…”
Section: Interaction Mechanismsmentioning
confidence: 99%